Inovasi Pembelajaran Model PBL dengan Desain FILA Chart Berbantuan Mindmaple Terhadap Keterampilan Metakognitif - Utami, Kurnia; Inayah, Ghina Nur; Supriatno, Bambang; Riandi, Riandi (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
This study aims to determine the effect of applying the Problem Based Learning (PBL) model with the FILA chart design with the aid of MindMaple on the metacognitive skills of class XI high school students on the excretory system material. This research was conducted at SMA Negeri 1 Palembang. The research method used is Quasi Experimental Design with the research design of Nonequivalent Control Group Design. Determination of the research sample using the Simple Random Sampling technique so that class XI IPA 6 was selected as the control class, XI IPA 7 as the experimental class, and XI IPA 8 as the placebo class with a total of 36 students in each class. Metacognitive skills are measured through a pre-test and a post-test with the instrument 3 essay questions with cognitive levels C4 to C6 which has been tested for validity and reliability. Data were analyzed using SPSS 25 program, hypothesis testing using ANCOVA test. The results of the ANCOVA test analysis showed that the application of the Problem Based Learning (PBL) model with the FILA chart design assisted by Mind Maple had a significant effect on the metacognitive skills of students at SMA Negeri 1 Palembang. Next The average results of the metacognitive skills final test scores sequentially show that the application of the PBL model with the FILA chart design with the aid of MindMaple is better than the application of the conventional learning model with the FILA chart design with the aid of MindMaple and conventional classes in improving students' metacognitive skills